METHODS FOR THE TREATMENT OF HYPERTENSION VIA TRANSCRANIAL-FOCUSED-ULTRASOUND - LEA-BANKS, Harriet; HYNYNEN, Kullervo (2025)
A minimally invasive method for the reduction of hypertension is provided using focused ultrasound. After injection of ultrasound-responsive nanodroplets loaded with a therapeutic agent (e.g. barbiturates), focused ultrasound is delivered to a norepinephrine-producing region, such as the periaqueductal gray region, thereby locally releasing the therapeutic agent payload from the nanodroplets and achieving a therapeutic reduction in blood pressure. Acoustic emissions from vaporizing droplets may be employed, for example, to infer one or more therapeutic parameters based on a pre-established correlation. For example, plasma hormone content and/or the change in blood pressure may be inferred, thereby providing a means of real-time treatment monitoring. The present example methods may be employed to achieve a reduction in blood pressure for subjects exhibiting drug-resistant hypertension.